Mental health among children and adolescents: Construct validity, reliability, and parent-adolescent agreement on the 'Strengths and Difficulties Questionnaire' in Chile. - Jorge Gaete (PLoS ONE, 2018)
The Strengths and Difficulties Questionnaire (SDQ) is a screening tool used to measure psychological functioning among children and adolescents. It has been extensively used worldwide, but its psychometric properties, such as internal structure and reliability, seem to vary across countries. This is the first study exploring the construct validity and reliability of the Spanish version of SDQ among early adolescents (self-reported) and their parents in Latin America. A total of 1,284 early adolescents (9-15 years) and their parents answered the SDQ. We also collected demographic variables. A confirmatory factor analysis was conducted to assess the latent structure of the SDQ. We also used the multitrait-multimethod analysis to separate the true variance on the constructs from variance resulting from measurement methods (self-report vs. parent report), and evaluated the agreement between adolescents and their parents. We found that the original five-factor model was a good solution and the resulting sub-scales had good internal consistency. We also found that the self-reported and parental versions of SDQ provide different information, which are complementary and provide a better picture of the emotional, social, and conduct problems of adolescents. We have added evidence for the construct validity and reliability of the Spanish self-reported and parental SDQ versions in a Chilean sample.